Gender Differences in Depressive Symptoms in Thai Individuals with Depressed Mood and/or Anhedonia: A Differential Item Functioning Approach - Manit Srisurapanont (2018)
© 2016, Springer Science+Business Media New York. This study used the item response theory-based log-likelihood-ratio technique for differential item functioning (IRT-LR DIF) to determine gender differences in seven add-on major depressive episode criteria in Thai people living in community. Of a population of 17,480 Thai people living in community, 322 men (3.79%) and 487 women (5.63%) currently were of depressed mood and/or anhedonia. Of seven symptoms, only cognitive deficit had a statistically significant DIF (G2of 7.3, df = 2, p = 0.007; Benjamini-Hochberg adjusted p = 0.049). The uniform DIF suggested that men had a significantly but marginally lower threshold value for endorsing cognitive deficit than women (threshold difference = −0.25). While the discrimination parameters of this cognitive symptom were greater than 2.0 (men = 2.10 and women = 2.29), their difference was as low as −0.19. Most depressed symp-toms have similar criterion functioning in both genders. However, Thai men may be more likely to have a cognitive deficit than their female counterparts.